COMPARATIVE ANALYSIS OF THE MOVEMENT MECHANISMS OF THE LOWER FEEDING ELEMENT IN A SEWING MACHINE - KOROBCHENKO, YEVHEN; HOROBETS, VASYL; DVORZHAK, VOLODYMYR (Herald of Khmelnytskyi National University. Technical sciences, 2025)
This study presents a comprehensive kinematic analysis of several material feed mechanisms used in sewing machines, including typical lever systems MI, M2, M3, as well as a newly proposed mechanism M4. The main objective of the research was to evaluate the effectiveness of these mechanisms in implementing the innovative feeding method and device developed by the authors to improve the material transportation process in industrial sewing equipment. The kinematic characteristics of the mechanisms were investigated using classical methods of mechanism and machine theory.Calculations and diagram construction were performed using the Mathcad software environment. During the study, the motion trajectories of the feeding elements and kinematic synchronograms were constructed. The evaluation criteria were based on the kinematic parameters of the lower feeding element, which significantly influence the performance of the new material feeding device. In particular, the following were considered; the maximum inclination angle of the tangent to the surface of the feeding element relative to the feeding direction; the horizontal velocity component y of the feeding elements at the moment of magnetic decoupling; the maximum positive horizontal acceleration a, of the upper feeding element during the working stroke; and the impact loading intensity on the upper feeding element, represented by a vertical jenk analogue. These parameters are critical for ensuring the efficient operation of the proposed device, which is based on magnetic interaction between the upper (neodymium magnet) and lower feeding elements. The proposed method and device aim to address the issue of relative material laver displacement (fabric shifting), which is one of the major problems in sewing production. The analysis showed that mechanism M4 is the most suitable for implementing the new method, although standard mechanisms (MI, M2, M3) may also be used with proper design adjustments. The obtained kinematic criteria and synchronograms will serve as input data for further design calculations of the device, facilitating its adaptation to conventional sewing machines.